Investigating Approaches Utilized by Instructors to Navigate Classroom Organization Issues in Higher Education Environments - Khan, Erum Aslam; Majeed, Sehrish; Hussain, Sarfraz; Tanveer, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
The primary goal of the study was to investigate the perspectives of instructors regarding strategies for managing classroom organization challenges in a higher education setting. The researcher selected a sample of 478 respondents by using a simple random sampling technique from six universities operating in Multan district. The study employs a quantitative approach, collecting data through a questionnaire. 348 questionnaires from the 478 instructors were collected. The response rate was 73.23%, which was acceptable for survey research. For the analysis of data, the researcher applied both descriptive and inferential statistics. Average mean and standard deviations were employed to examine the opinion of higher education institution instructors about the frequency of use of approaches and effectiveness of these approaches. A t-test was employed from inferential statistics for finding the opinion of higher education institution instructors on the basis of gender. Percentage analysis was conducted for the analysis of approaches through rank-order. Thematic analysis method was used for the examination of open-ended questions. The study found that higher education institution instructors often use clear voice, question-answer strategies, and active student-instructor interaction to address classroom organization issues. Other approaches include planning lessons, treating all learners equally, arranging the classroom well, improving familiarity, and practicing instructional techniques. However, the use of rules based on conditions, time-out approaches for violent behavior, and rules for penance and penalties was rare.